Impacts of ocean acidification in a warming Mediterranean Sea: An overview - Lacoue-Labarthe, Thomas; Nunes, Paulo A.L.D.; Ziveri, Patrizia; Cinar, Mine; Gazeau, Frédéric; Hall-Spencer, Jason M.; Hilmi, Nathalie; Moschella, Paula; Safa, Alain; Sauzade, Didier; Turley, Carol (Regional Studies in Marine Science, 2016)
International audience Mediterranean Sea fisheries supply significant local and international markets, based largely on small pelagic fish, artisanal fisheries and aquaculture of finfish (mainly seabass and seabream) and shellfish (mussels and oysters). Fisheries and aquaculture contribute to the economy of countries bordering this sea and provide food and employment to coastal communities employing ca 600,000 people. Increasing temperatures and heat wave frequency are causing stress and mortality in marine organisms and ocean acidification is expected to worsen these effects, especially for bivalves and coralligenous systems. Recruitment and seed production present possible bottlenecks for shellfish aquaculture in the future since early life stages are vulnerable to acidification and warming. Although adult finfish seem able to withstand the projected increases in seawater CO2, degradation of seabed habitats and increases in harmful blooms of algae and jellyfish might adversely affect fish stocks. Ocean acidification should therefore be factored into fisheries and aquaculture management plans. Rising CO2 levels are expected to reduce coastal biodiversity, altering ecosystem functioning and possibly impacting tourism being the Mediterranean the world’s most visited region. We recommend that ocean acidification is monitored in key areas of the Mediterranean Sea, with regular assessments of the likely socio-economic impacts to build adaptive strategies for the Mediterranean countries concerned.